Ejecución presupuestaria del GAD parroquial Mata de Cacao periodo 2021. - Guzmán Ledesma, Roxana Araceli (2022)
GAD Parroquial de Febres Cordero is a public sector institution that enjoys both administrative, political and financial independence as stated in the Constitution, and the Autonomy and Decentralization Territorial Organic Code, in addition to being the entity in charge of providing services that help the development of the parish community, fulfilling the objectives established in its mission and vision, in addition to the plans established as a public entity for the period 2021, this institution is taken as the entity under study for the topic: "Budget Execution of the GAD Mata de Cacao Parish Period 2021”. Research that is marked in the research line of the Accounting and Auditing, Financial Management, Administrative, Tax, Audit, Control career, with the Financial Management and Social Commitment subline, whose objective is to analyze and verify that the budget allocations that the entity receives have been executed in their entirety and to know what were the destinations of these resources, with an inductive-deductive approach methodology using as a tool the interview and analytical observation of the budgetary cells of the institution. Obtaining as results of the investigation that the budget was executed in 88.85% of its totality, and leaving the budget item of Investment Expenses with an increase of 57.84%, due to debts acquired for the improvement of community works, which were covered with items from other items that were not fully spent.